Auto-luminescence in seedlings: possible indicators for the gravimetric tide? - Gallep, Cristiano de Mello (Frontiers in Photonics, 2024)
Germinating seedlings emit light in the visible range, spontaneously, and those emissions are related to metabolism and reactive-oxygen species (ROS) processes. Several series of germination tests had such biological auto-luminescence (BAL) recorded in controlled conditions, fostering applications for non-invasive, real-time evaluation of seedling's germinability and vigor, when submitted to chemical and/or physical perturbations. But long term analysis of BAL time-series of control samples, run in different places in the earth globe, also reveals that their BAL signal (and so their metabolism) does somehow follow the local gravimetric tide (g-tide) time profile, ie. the small daily and monthly variations of the gravity acceleration due the relative positioning of Sun and Moon to the Earth surface.The gravimetric tide is something all things are exposed -fluid or not -and it is a variable one cannot control inside a normal, laboratory standing over the Earth crust. All things have evolved on Earth under such tedious but pervasive cycles with periods from ~12.2h up to 28d -ie., the Moon cycle. As such tide-like cycles occur in living beings of different types, from the simplest bacteria to the complex human-being, we speculate that the water availability at molecular level would be a physical sufficient factor able to somehow modulate bio-activity, by enabling protein folding and all metabolic chains in need of synchronized organization to fit into the external environmental conditions.Here, we summarize published results of seedling's BAL with such cycle patterns resembling the gtide -in Limeira/BR, Prague/CZ, Leiden/NL and Hamamatsu/JP -and discuss possible implications of this phenomena for chronobiological studies.